Implementation of Evidence‐Based Practice From a Learning Perspective. Issue 3 (9th March 2017) - Nilsen, Per; Neher, Margit; Ellström, Per‐Erik; Gardner, Benjamin
ABSTRACT: Introduction: For many nurses and other health care practitioners, implementing evidence‐based practice (EBP) presents two interlinked challenges: acquisition of EBP skills and adoption of evidence‐based interventions and abandonment of ingrained non‐evidence‐based practices. Aims: The purpose of this study to describe two modes of learning and use these as lenses for analyzing the challenges of implementing EBP in health care. Methods: The article is theoretical, drawing on learning and habit theory. Results: Adaptive learning involves a gradual shift from slower, deliberate behaviors to faster, smoother, and more efficient behaviors. Developmental learning is conceptualized as a process in the "opposite" direction, whereby more or less automatically enacted behaviors become deliberate and conscious. Conclusion: Achieving a more EBP depends on both adaptive and developmental learning, which involves both forming EBP‐conducive habits and breaking clinical practice habits that do not contribute to realizing the goals of EBP. Linking Evidence to Action: From a learning perspective, EBP will be best supported by means of adaptive learning that yields a habitual practice of EBP such that it becomes natural and instinctive to instigate EBP in appropriate contexts by means of seeking out, critiquing, and integrating research into everyday clinical practice as well as learning new interventions best supported by empirical evidence. However, the context must also support developmental learning that facilitates disruption of existing habits to ascertain that the execution of the EBP process or the use of evidence‐based interventions in routine practice is carefully and consciously considered to arrive at the most appropriate response.